General Maslofski'nin umumi harpte Kafkas Cephesi eserinin tenkidi - Maslovskiy, Evgeniy Vasileviç, Rus General, 1877-1965. (Ankara)
2 c. (1. c. [7], 523 s. ; 2. c. 23 kroki, 2 cetvel, 1 grafik, 73 s. zeyl)